Discontinuous deformation analysis (DDA) simulations of crack propagation, branching and coalescence in brittle materials under dynamic loading. (December 2022) - Li, Chunyu; Ning, Youjun; Liu, Xinlian
Highlights: A sub-block element DDA method is applied and verified for the simulations crack initiation, propagation, and coalescence in brittle materials. Examples including the Kalthoff-Winkler experiment, the cracking in a tensile loaded plate, and the double-hole blasting of a rectangular plate are reproduced. Problems including the mesh size, loading intensity, crack propagation velocity, and the effect of guiding hole are investigated. Abstract: Cracking in brittle materials under dynamic loading is widely encountered in engineering. The discontinuous deformation analysis (DDA) is a numerical method initially proposed to calculate the static and dynamic behaviors of discrete deformable-block systems, which can also be used to simulate the cracking failure of materials via the sub-block element approach. In the present work, a sub-block element DDA method is applied to simulate the crack evolution problems in brittle materials under dynamic loading. The tensile and shear cracking along the artificial joints between glued sub-block elements is judged based on the stress levels of adjacent sub-blocks by the maximum tensile strength criterion and the Mohr-Coulomb criterion, respectively. Three numerical examples including the Kalthoff-Winkler experiment, the cracking in a tensile loaded plate and the double-hole blasting of a rectangular plate are simulated. The effect of the mesh size for the Kalthoff-Winkler experiment, the loading intensity for the Kalthoff-Winkler experiment and the tensile loaded plate, and the influence of the guiding hole for the double-hole blasting plate are specially investigated. The DDA simulation results of cracking routes and velocity are reasonably consistent with the corresponding experimental results or numerical results by other methods, which manifests the ability of the applied sub-block element DDA method in the simulations crack propagation, branching and coalescence of brittle materials under dynamic loading.